EFFORTS TO PREVENT VIOLENT CONFLICT AMONG INMATES IN THE CLASS IIA ABEPURA CORRECTIONAL FACILITY - Marani, Sarlan Alberto; Rahayu, Mulyani (Universitas Nusa Cendana, 2025)
Prisoner conflicts have become a serious issue often caused by overcrowding, group competition, and inadequate facilities and management in correctional facilities. These factors create tensions that lead to physical violence, negatively impacting prisoners, officers, and overall security. Violent conflicts also worsen the rehabilitation conditions of prisoners, hinder training programs, and increase the risk of disturbances. Limited space, scarce resources, and competition for facilities such as access to clean water and healthcare services further exacerbate the situation. Prisoners with different backgrounds and interests often clash, leading to an increase in violent incidents such as beatings and stabbings. To address this issue, the research adopts the mediation theory proposed by Christopher Moore. Mediation is conducted by encouraging effective communication, interest-based approaches, and collaboration among the conflicting parties. In the context of prisons, mediation plays a crucial role in reconciling prisoners involved in conflict before the situation escalates into greater violence. Correctional officers are also encouraged to carry out more intensive supervision and improve their skills in handling high-risk situations. The research findings are expected to provide recommendations for prison administrators in formulating more effective policies to prevent violent conflicts. With the application of mediation theory and adequate preventive measures, it is hoped that conflicts can be minimized, creating a safer and more conducive prison environment for the rehabilitation process. Keywords: Conflict Prevention; Prisoner Violence; Mediation; Overcrowding; Prisoner Rehabilitation